The use of a GPS as a measurement tool of velocity in a progressive test. Application on a wheel-chair athletics test - Ferrer, V.; Juray, M. M.; van Nieuwenhuizen, M. T. M.; Banquells, M.; Drobnic, F. (Archivos de medicina del deporte, 2008)
Introduction: Determination of velocity during the tests is sometimes depending on the correct wheel measurement and the friability of the speedometer system used on the wheel chair or bycicle. Modern GPS, and also other devices as pulsometers with GPS have arrived to the athletics measurement fi eld. Validation and usefulness of those systems are needed. Objective: Validate a GPS system to control mean velocity during a progressive exercise test. A second objective is the applicability of this system on a fi eld test on wheel chair athletes. Method: We use a GPS system - SPI 10, for photoelectric cells Tag Heuer with telemetry, chronoprinter, an odometer and a bicycle. The track fi eld was measured on the fi rst road with the odometer and was 402,60m. From one cell to other the distance was from 0cell to the fi rst 101,3m: from the 1 to the 2nd 100m: from the 2nd to the 3rd 101,3 and from the 3rd to the 0 100m. To locate the cells by the GPS stayed stopped during 15 seconds on every cell (0 to 4th). The test consisted on cycling at four different velocitiea for 2 laps (800 m) mantaining a constant velocity on every lap. First lap 15 - 16 Km/h, 2nd lap 19 - 20 Km/h, 3rd lap 22 - 23 Km/h, and 4th between 25 - 26 Km/h. Results: Table 1 and Figure 1. Discussion/Conclusions: Velocity obtained from the GPS used, shows a correct correlation with the velocity measured by the photocells for all the velocities explored. The use of GPS seems very useful for athletes who us wheels for their sport on training, testing or competition.